PENGARUH ELECTRONIC WORD OF MOUTH, CELEBRITY ENDORSER DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN THE ORIGINOTE (STUDI KASUS PADA PENGGUNA MEDIA SOSIAL TIKTOK) - Candraningtyas, Disa; Rachman , Adryan (Publika Citra Media, 2024)
The increasingly sophisticated development of today's technology means that interest in shopping online is increasing, one of the social media platforms, Tik Tok, also does not want to be left behind in terms of technology to expand its market, therefore Tik Tok has added the Tik Tok shop and live streaming shopping features to support needs. the market will shop online. However, when the TikTok shop is down, there are no live sales. This research aims to find out what can make people decide to buy The Originote products even though the TikTok shop is closed, and whether there is an influence between (1) electronic word of mouth on the decision. purchases, (2) celebrity endorsers on purchasing decisions, and (3) brand image on purchasing decisions. The method for conducting this research is quantitative using multiple regression analysis with data collection techniques, namely a questionnaire using the Roscoe formula to obtain 54 samples. The population used as a sample is TikTok users who are aware of The Originote products. The research results show that electronic word of mouth, celebrity endorser, and brand image simultaneously influence purchasing decisions.